The supported grid tool for measuring an applicability of medical dataset visualization - 200667 Ibrahim Salim Najam; Muhammad Shafie Abd. Latif, supervisor (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Sains (Sains Komputer) ) - Universiti Teknologi Malaysia, 2008